First Step in Exploration of Fe–Ga–N System for Efficient Crystallization of GaN at High N2 Pressure. Issue 13 (30th April 2018) - Sadovyi, Petro; Sadovyi, Bogdan; Bockowski, Michal; Dziecielewski, Igor; Porowski, Sylwester; Grzegory, Izabella
Abstract : According to the existing data, iron is a very efficient solvent for nitrogen. In this work, the results of first steps toward crystallization of GaN from Fe‐based solutions at 1 GPa N2 pressure are reported. Melting of Fe at 0.88 GPa N2 pressure is studied by differential thermal analysis (DTA) which shows a strong (≈200 °C) decrease of melting temperature as compared to the well‐established value of 1570 °C for pure Fe at 0.88 GPa at inert atmosphere. The N content of about 11.9 at.% is found by ON836 LECO analyzer in the Fe samples after DTA. It means that the observed drop of T m (Fe) is related to the high solubility of nitrogen in Fe metal. Also the dissolution of GaN in Fe in 1370–1480 °C temperature range is studied. Encouragingly high (22–30 at.%) solubilities of Ga (direct measurement) and most probably, as high for N (evaluated from mass balance) are found. Abstract : Experiments show that iron can be a solvent in GaN crystallization processes at 1 GPa N2 pressure, whereas Fe melts at about 200 °C below the decomposition temperature of GaN (1500 °C). N solubility in Fe is 12 at.% at T  = 1380 °C and p  = 1 GPa. Temperature dependence of GaN solubility in Fe at 1 GPa N2 pressure is studied. New GaN crystals grow from the Fe–Ga–N solution during cooling.